Pelvic Stability Training on Movement Control, Pelvic Muscle Strength, Walking Speed, and ADL in Post-Stroke Patients: CASE STUDY - Deny Prasetyanto; Dodik Hartono; Ainul Yaqin Salam (J I K O (Jurnal Ilmiah Keperawatan Orthopedi), 2023)
A cute hemiparesis can develop in response to a variety of cerebral diseases including intracerebral hemorrhage and ischemic stroke, Pelvic stability training is an exercise protocol designed based on neurophysiological and biomechanical aspects of pelvic stability designed based on the performance of each patient so as to increase pelvic stability. pelvic stability training is carried out for 30 minutes, 3 times per week, for 3 weeks. Pelvic stability training (PST) exercises have been shown to improve motor function in the lower extremities both in muscle strength, and to help meet ADL.